Protecting Women's Reproductive Rights in Restrictive States : The Impact of NGOs - Iakupova, Aida; Trávníčková, Zuzana, 1977-; Votoupalová, Markéta; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Abortion law reform remains a contentious issue worldwide, with some countries expanding access and others tightening restrictions. This thesis examines the role of non-governmental organizations (NGOs) in shaping abortion legislation, particularly in politically and culturally restrictive contexts. It explores how NGOs promote reproductive rights and what strategies they use to influence change. The research applies two frameworks: the Advocacy Coalition Framework (ACF) and the Human Rights-Based Approach (HRBA) to analyze how NGOs build alliances, frame abortion as a human rights issue, and navigate institutional barriers. A comparative case study method is used to examine six countries: Argentina, Colombia, South Korea, Thailand, San Marino, and Finland, that reformed their abortion laws between 2020 and 2024. The findings show that NGOs employed a range of strategies, including strategic litigation, coalition-building, and public campaigns. However, legal reform did not always lead to practical access. While implementation progressed in Finland and San Marino, significant barriers remained in South Korea and Thailand due to stigma, lack of regulation, and institutional resistance. The thesis concludes that effective advocacy requires more than legal change, it depends on sustained engagement, cultural framing, and cross-sectoral coordination.
Vedoucí práce: Zuzana Trávníčková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses